Exploring the lower rates of entry into undergraduate engineering among female students through the application of the reasoned action approach. (4th May 2022) - Moloney, Grace; Ahern, Aoife
ABSTRACT: This thesis examines why, despite extensive research, women are underrepresented in engineering courses in many countries, including Ireland. The reasons for this underrepresentation are not well-understood. This study seeks to contribute to the understanding of women's decision-making regarding their studying engineering, through the application of a behavioural model, the Reasoned Action Approach. It is expected that this insight may improve the effectiveness of intervention programmes aimed at increasing the number of women studying undergraduate engineering. This study is based on an analysis of data collected through surveys. The survey included male and female students in their 5th or 6th-year working towards their Leaving Certificate exams. The key conclusion of this research is that a multitude of factors are at play when it comes to women's lower entry into undergraduate engineering. These factors include lower levels of confidence in ability in subjects related to engineering, negative attitudes towards studying engineering and a lack of encouragement towards the study of engineering required by many women to overcome the off-putting nature of the male occupational image of engineering.